Risk Averse Metaheuristic Hybrid Solution Approach to Vehicle Routing Problem of Hazardous Materials Through the Combination of Game Theory and Tabu Search - Aslan, Hakan; Bell, Michael G.h (Fırat University, 2026)
Because they have become an integral part of our daily lives, large quantities of hazardous materials are produced and transported each year. In most industrial societies, life without hazardous materials has become almost unimaginable. Hazardous materials are defined as substances that, during transportation, have the potential to pose adverse effects or risks to public health, safety, or property due to their quantity or form. In this context, hazardous materials or products include explosives, gases, flammable and oxidizing substances, toxic and infectious materials, as well as radioactive, corrosive substances and their associated hazardous wastes. The safe transportation of hazardous materials is considered a comprehensive and multidimensional issue, influenced by various legal and physical factors, as well as the numerous risks that vehicles may encounter during transit. Increasing environmental awareness of the potential impacts of hazardous material accidents on public health has significantly heightened both academic and institutional interest in this field. This study proposes a risk-averse solution to the hazardous material transportation problem through a model developed by integrating the Tabu Search algorithm with a game theory–based approach. Within the model, the dispatcher aims to minimize the expected loss under the worst possible conditions in the event of a disruption in any link of the distribution network. In this framework, the expected cost determined through Nash equilibrium is evaluated as an effective and practical analytical tool for strategic decision-making in the selection of safe routes for hazardous material transportation.

Günlük yaşamımızın ayrılmaz bir parçası haline gelmelerinin bir sonucu olarak, her yıl büyük miktarlarda tehlikeli madde üretilmekte ve taşınmaktadır. Sanayi toplumlarının çoğunda, tehlikeli maddeler olmadan bir yaşam neredeyse tahayyül edilemez hâle gelmiştir. Tehlikeli maddeler; taşınma sürecinde halk sağlığı, kamu güvenliği ya da taşınmaz mallar üzerinde olumsuz etkiler veya riskler yaratma potansiyeline sahip miktar ve formda bulunan maddeler olarak tanımlanır. Bu bağlamda, tehlikeli maddeler veya ürünler; patlayıcı, gaz hâlinde, yanıcı, oksitleyici, toksik, bulaşıcı, radyoaktif ya da aşındırıcı özellik gösteren maddeler ile bunlara ait tehlikeli atıkları kapsamına almaktadır. Tehlikeli maddelerin güvenli taşınması; sürece etki eden yasal ve fiziksel faktörler ile taşıma araçlarının maruz kalabileceği çeşitli riskler nedeniyle kapsamlı ve çok boyutlu bir sorun alanı olarak değerlendirilmektedir. Tehlikeli madde kazalarının halk sağlığına yönelik olası etkilerine karşı artan çevresel duyarlılık, tehlikeli madde taşımacılığı konusuna yönelik akademik ve kurumsal ilgiyi önemli ölçüde artırmaktadır. Bu makale, oyun teorisi temelli bir yaklaşımla tabu arama algoritmasının entegrasyonu sonucu geliştirilen model üzerinden, tehlikeli madde taşımacılığı problemine yönelik riskten kaçınan bir çözüm önermektedir. Model kapsamında, dağıtım görevlisi, sevkiyat ağındaki herhangi bir bağlantıda problem oluşması durumunda, olası en olumsuz koşullar altında ortaya çıkabilecek beklenen zararı minimize etmeyi hedeflemektedir. Bu çerçevede, Nash dengesi aracılığıyla belirlenen beklenen maliyet fonksiyonu, tehlikeli madde taşımacılığında güvenli güzergâh seçimine yönelik stratejik kararların analizinde etkili ve pratik bir çözüm aracı olarak değerlendirilmektedir.
Oyun Teorisi ve Tabu Araması Yoluyla Tehlikeli Maddelerin Araç Rotalama Problemine Risk Kaçınımlı Metasezgisel Hibrit Çözüm Yaklaşımı
Keywords: Transportation Engineering; Ulaştırma Mühendisliği